2005
DOI: 10.1021/ja054199x
|View full text |Cite
|
Sign up to set email alerts
|

Response of a Designed Metalloprotein to Changes in Metal Ion Coordination, Exogenous Ligands, and Active Site Volume Determined by X-ray Crystallography

Abstract: The de novo protein DF1 is a minimal model for diiron and dimanganese metalloproteins, such as soluble methane monooxygenase. DF1 is a homodimeric four-helix bundle whose dinuclear center is formed by two bridging Glu side chains, two chelating Glu side chains, and two monodentate His ligands. Here, we report the di-Mn(II) and di-Co(II) derivatives of variants of this protein. Together with previously solved structures, 23 crystallographically independent four-helix bundle structures of DF1 variants have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 51 publications
2
54
0
1
Order By: Relevance
“…The ground-breaking work of DeGrado and coworkers (17)(18)(19)(20) has led to the development of well packed helix bundle proteins with natural-like sequences and stabilizing interactions. In their work, and pioneering work from other laboratories, a specific fold has been achieved via the formation of tertiary hydrogen bonds (20)(21)(22)(23), crystal contacts (18,24), disulfide bonds (25,26) or favorable charge-charge interactions (19,20,23,24,26,27). Previous work toward simplifying proteins has shown that a native-like Src homology 3 fold can be achieved with chiefly five different residues (although 13 in total) (28), and a four-helix bundle protein can be formed from only nine different residues (29).…”
Section: The Presence Of An Aromatic Ring At the C Terminus Is Requirmentioning
confidence: 99%
“…The ground-breaking work of DeGrado and coworkers (17)(18)(19)(20) has led to the development of well packed helix bundle proteins with natural-like sequences and stabilizing interactions. In their work, and pioneering work from other laboratories, a specific fold has been achieved via the formation of tertiary hydrogen bonds (20)(21)(22)(23), crystal contacts (18,24), disulfide bonds (25,26) or favorable charge-charge interactions (19,20,23,24,26,27). Previous work toward simplifying proteins has shown that a native-like Src homology 3 fold can be achieved with chiefly five different residues (although 13 in total) (28), and a four-helix bundle protein can be formed from only nine different residues (29).…”
Section: The Presence Of An Aromatic Ring At the C Terminus Is Requirmentioning
confidence: 99%
“…[4] In particular, we have asked whether the same metal can be bound to structurally related peptides with identical first-coordinationsphere ligands derived from the protein, but in one case form a trigonal structure and in a second case form a fourcoordinate pseudo-tetrahedral environment. [4] The relative importance of a metals geometric preference and the inherent protein structure is fundamental to understanding the folding, [5][6][7][8] stability, [9,10] and conformational changes [4,5,11] of metalloproteins, and hence the control of such site discrimination has been an important objective of protein design studies. The peptides described herein are variants of the TRI family of peptides shown in Table 1.…”
mentioning
confidence: 99%
“…There have been previous examples of using peptides to form internal structures with specific properties. For example, a de novo designed four helix bundle protein was engineered to provide an internal metal binding site, but in this case, the characteristics of the internal cavity was largely determined by peptide-peptide contacts and the protein was folded even in the absence of metal ions (16). Pairs of Alacoil dimers related by the pseudo two-fold axis aligned with the octamer bundle axis (z in Fig.…”
Section: Resultsmentioning
confidence: 99%